2012
DOI: 10.4067/s0718-40262012000300010
|View full text |Cite
|
Sign up to set email alerts
|

Fístula colovesical secundaria a enfermedad diverticular: cirugía laparoscópica electiva

Abstract: Colovesical fi stula: laparoscopic surgery Aim: Colovesical fi stula is a severe complication associated to neoplastic or infl ammatory colon disease. Most common procedure is open surgery. We report a case of colovesical fi stula secondary to diverticular disease treated with a laparoscopic approach. Methods: A 64-year-old man was seen with a known colonic diverticular disease, type 2 diabetes mellitus and recurrent urinary tract infection. He complained of lower abdominal pain, dysuria, and pneumaturia. A CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The most common cause of colovesical fistula is diverticular disease of the sigmoid colon (66-75% of cases). [3][4][5] The underlying mechanism is the direct extension of ruptured diverticulum or the erosion of a peridiverticular abscess into the bladder, and the mechanism by which colon cancer can take the bladder abscess from the tumor or infiltrate the bladder dome. Most patients (> 90%) with colovesical fistula usually present with recurrent urinary infections and dysuria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common cause of colovesical fistula is diverticular disease of the sigmoid colon (66-75% of cases). [3][4][5] The underlying mechanism is the direct extension of ruptured diverticulum or the erosion of a peridiverticular abscess into the bladder, and the mechanism by which colon cancer can take the bladder abscess from the tumor or infiltrate the bladder dome. Most patients (> 90%) with colovesical fistula usually present with recurrent urinary infections and dysuria.…”
Section: Discussionmentioning
confidence: 99%
“…(2,3) In any case, FCVs are observed in very advanced stages of neoplastic diseases. (4,5) This article presents a case of a patient whose initial manifestations of cancer of the colon turned out to be a colovesical fistula. As this is a rare entity in surgical practice and is an unusual manifestation of left colon cancer, we made this presentation.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 These studies suggested that laparoscopic surgery is associated with lower surgical stress which translates into lower morbidity, reduced blood loss, less pain, and shorter length of stay. [15][16][17][18][19][20][21] It is a strong recommendation to perform elective minimally invasive colectomy for non-complicated diverticulitis. 7,8 Nevertheless, for the specific group of patients with CVF, there is no evidence to support laparoscopic over open surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple case series and cohort studies have reported the feasibility and safety of laparoscopic surgery in the treatment of CVF 13,14 . These studies suggested that laparoscopic surgery is associated with lower surgical stress which translates into lower morbidity, reduced blood loss, less pain, and shorter length of stay 15–21 …”
Section: Introductionmentioning
confidence: 99%